2011
DOI: 10.1007/s00702-011-0733-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology, neuroimaging or motor phenotype in diagnosis of Parkinson’s disease-dementia: which matters most?

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder affecting not only the motor system but also the cognitive and behavioral domains. Although there are many studies addressing the issue of cognition, a universally recognized method to diagnose patients with dementia is still lacking. The aim of this study was to determine which neuropsychological test is the most reliable in the diagnosis of dementia in PD and to establish if mini mental state examination (MMSE) is enough to detect this condition. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It has also been suggested that the transition from PD to PDD is characterized by an addition of more posterior cortical cognitive symptoms, such as problems in episodic memory, visuospatial deficits, and language processing, to the more fronto‐striatally mediated executive/attentive impairments . This has been corroborated by a recent study , showing that PDD patients were impaired compared with non‐demented patients on measures of attentive/executive functions (e.g. verbal fluency) as well as those of learning and episodic memory.…”
Section: Discussionmentioning
confidence: 75%
“…It has also been suggested that the transition from PD to PDD is characterized by an addition of more posterior cortical cognitive symptoms, such as problems in episodic memory, visuospatial deficits, and language processing, to the more fronto‐striatally mediated executive/attentive impairments . This has been corroborated by a recent study , showing that PDD patients were impaired compared with non‐demented patients on measures of attentive/executive functions (e.g. verbal fluency) as well as those of learning and episodic memory.…”
Section: Discussionmentioning
confidence: 75%
“…The verbal fl uency tasks are frequently used to evaluate cognitive changes, characterize the performance profi les in healthy aging and in neurodegenerative diseases (Di Biasio et al, 2012;Martyr et al, 2012). Fast and easy to administer, these tasks can be managed individually or as being present in some assessment protocols (Dubois, Slachevsky, Litvan, & Pillon, 2000;Fillenbaum et al, 2008).…”
mentioning
confidence: 99%
“…34 Moreover, the study by Di Biasio et al also recommended the use of an extensive neuropsychological battery in the diagnosis of dementia in patients with PD. 10 Other neuropsychological assessment batteries include RVR, BD, DS, and FOME. These tests usually test multiple separate cognitive domains that may collapse to form composite measures.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of an extensive neuropsychological battery has been recommended. 10 The objective of the present study was to determine the specificity, sensitivity, and accuracy of various neuropsychological tests, including Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Block Design (BD), Fuld Object Memory Evaluation (FOME), Digit Span (DS), and Rapid Verbal Retrieve (RVR), and any of their combinations in Chinese patients with PD, and to identify the best short screening test for dementia in PD in order to facilitate clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%